Increased body growth rates of northern pike (Esox lucius) in the Baltic Sea : importance of size-selective mortality and warming waters - Berggren, Terese (SLU/Dept. Of Aquatic Resources, 2019)
The northern pike, Esox lucius Linnaeus (1758), is a highly valuable species in recreational fishing, and plays a vital role as a keystone predator in the structuring of fish communities in temperate lakes and brackish waters. Ma-jor declines of pike in the Baltic Sea have been recorded, particular of larger pikes, which may have cascading effects on abundances of lower ecosys-tem compartments. Despite the decline in pike densities in the Baltic Sea there is a lack of data on how pike populations respond to climate change (i.e. warming waters) along with fishing-induced effects. In this thesis I focus on how pike body growth has changed over time across three areas with different history of fishery management. By using time series of back-calcu-lated body lengths extending from the 1960s until today this study shows that the body growth of pike in the Baltic Sea has changed over time and differs between study areas. Observations in all three areas are consistent with the hypotheses that body growth has increased over time, partly due to warming waters, and that the no-take reserve has lower growth rate com-pared to fished areas. Despite the increase in growth rate, it is evident that the mean length of pike as well as the length of the largest 5% have de-creased in all areas since the1980s. Rosa Lee’s phenomenon is clearly demonstrated in this study where immature pikes have increased over peri-ods and smaller pikes than average grow older and remain longer in the population. The decrease in number of large pike does not appear to be due to slower body growth but rather to size-selective mortality. In order to re-gain large pike along the Swedish coastline in the Baltic Sea, fisheries man-agement is needed that focuses on reduced mortality. Thus, fishing pres-sure needs to be proportional to growth rate in order to recruit larger individ-uals exceeding the maximum length limit of fishing.